PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI PADA DINAS PENDAPATAN DAERAH KOTA JAYAPURA - Sian Linda Lerebulan (Sekolah Tinggi Ilmu Ekonomi Port Numbay Jayapura, 2017)
This study aims to determine and analyze (1) whether job satisfaction and organizational commitment simultaneously have a significant effect on employee performance at the Jayapura City Revenue Service (2) whether job satisfaction and organizational commitment partially have a significant effect on employee performance at the Jayapura City Revenue Service ( 3) Which variable has a dominant influence on employee performance. This research was conducted at the Regional Revenue Service of Jayapura City. The data taken is primary data in the form of questionnaires, the sample in the study was 97 respondents, the data were analyzed using multiple linear regression analysis. The results of this study indicate that simultaneously all independent variables, both job satisfaction (X1) and organizational commitment (X2) have a positive and significant effect on the dependent variable or employee performance (Y) at the Jayapura City Regional Revenue Service. And partially shows all independent variables, both job satisfaction (X1) and organizational commitment (X2) partially and significantly affect the dependent variable or employee performance (Y) at the Jayapura City Regional Revenue Service. The more dominant variable that has an influence on work performance is the job satisfaction variable (X1)